Heritage Preservation : Museum Conservation and First Nations Perspectives - Clavir, Miriam (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2002)
This article focuses on the differing definitions museum conservators and First Nations have of “heritage preservation”. It explores differences at the level of the meta-narrative and in the details, focusing on several conservation concerns such as “what constitutes damage” and “should all objects be preserved”. In addition, the First Nations people quoted in this paper saw conservation as embedded in the museum context, and their opinions on museums and museum practice are also presented. The appropriateness of continuing to use the word “ethnographic” for collections from indigenous peoples as well as for the conservation subfield that conserves these collections is also explored. A considerable portion of this paper is devoted to First Nations viewpoints voiced in their own words.